The Akkadian Dialect of the Scribes of Amurru in the 14th-13th Centuries B.C. - Izre'el, Shlomo (1985)
Ph.D. Dissertation; Publication (probably under the title Amurru Akkadian - a Linguistic Study) planned for late 1988 or early 1989; in Hebrew with English summary; Supervisor: Anson F. Rainey